2020
DOI: 10.24018/ejbmr.2020.5.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Sector Development and its Effect on the Financial Markets in Developing Countries: The Case of Kosovo

Abstract: The purpose of this paper is to extract the important factors in the nature of insurance companies and their direct role in the economic and financial system development. This market study aims to analyse the insurance system in Kosovo by determining and then analysing its structure, the degree of concentration of insurance companies on the insurance market, their behaviour towards price, number of participants, companies operating in this market and types of products and services they provide. Our analysis ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…This means that pension funds in Nigeria stimulate the depth of the financial sector in Nigeria. The study also found that insurance funds do not have a significant effect on financial deepening, which is not in tandem with the findings of Baruti (2020). This implies that the increase or decrease in insurance funds will not affect the depth of the financial sector.…”
Section: Conclusion and Recommendationscontrasting
confidence: 50%
See 4 more Smart Citations
“…This means that pension funds in Nigeria stimulate the depth of the financial sector in Nigeria. The study also found that insurance funds do not have a significant effect on financial deepening, which is not in tandem with the findings of Baruti (2020). This implies that the increase or decrease in insurance funds will not affect the depth of the financial sector.…”
Section: Conclusion and Recommendationscontrasting
confidence: 50%
“…Lastly, further work needs to be done by the Nigerian Exchange Group to list companies. Baruti (2020) examined insurance sector development and its effect on the financial markets in Developing Countries: The case of Kosovo. The market study aimed to analyse the insurance system in Kosovo by determining and then analyzing its structure, the degree of concentration of insurance companies on the insurance market, their behaviour towards price, the number of participants, companies operating in this market and types of products and services they provide.…”
Section: Insurance Funds and Financial Deepeningmentioning
confidence: 99%
See 3 more Smart Citations